De la bienveillance en éducation. Évolution historique d'un concept et des pratiques associées - Loïc Chalmel (Université de Provence, 2018)
Can the concept of benevolence in education and training be regarded as an in-novo or a long-standing historical tradition transmitted as part of a cultural heritage? If the second possibility is accepted, the present article must give the reader a reading of the nature of the will. How then and when does the idea of benevolence in education come about? By what channels does it travel to us? What are the modalities of its development: capillarity, contagion, imitation, and amalgam? Who articulates it in actual practices? How, in the end, does the transmission take place and what are its instruments? The "veillance" faculty of the historian makes it possible to apprehend the modes of transmission of "benevolence" as intangible cultural heritage, the perennially of such a patrimony requiring the successive reappointments of commutants of practitioners.